2016
DOI: 10.20344/amp.6402
|View full text |Cite
|
Sign up to set email alerts
|

Condilomas Anogenitais numa Consulta de Doenças Sexualmente Transmissíveis: Centro de Saúde da Lapa - Lisboa, 2008 a 2014

Abstract: Introduction:Human papillomavirus infection is the most common sexual transmitted infection in the world, being associated with different diseases, namely anogenital warts, recurrent respiratory papillomatosis and anal, cervical, and oropharyngeal cancers. Among sexually active people, approximately 1% has anogenital warts, 90% of cases resulting from genotypes 6 and 11. Material and Methods: Patients diagnosed with first episode of anogenital warts from 2008 to 2014 in Lisbon's major venereology clinic were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…15 A third STI clinic reported 902 cases of anogenital condyloma between 2008 and 2014, of which 18.4% were diagnosed in MSM. 19 Another study conducted in a community clinic in Lisbon between 2008 and 2013 found 238 cases (9.8%) of gonorrhea and 158 (6.5%) of chlamydia. 20 Considering the ones who were infected, anorectal infection occurred in 38 (16%) of the ones infected by gonorrhea and 23 (14.6%) of the ones infected by chlamydia.…”
Section: Introductionmentioning
confidence: 98%
“…15 A third STI clinic reported 902 cases of anogenital condyloma between 2008 and 2014, of which 18.4% were diagnosed in MSM. 19 Another study conducted in a community clinic in Lisbon between 2008 and 2013 found 238 cases (9.8%) of gonorrhea and 158 (6.5%) of chlamydia. 20 Considering the ones who were infected, anorectal infection occurred in 38 (16%) of the ones infected by gonorrhea and 23 (14.6%) of the ones infected by chlamydia.…”
Section: Introductionmentioning
confidence: 98%
“…In other countries the prevalence of such infections is significantly higher and accounts for 196 cases per 100 000 of the population [6,21].…”
mentioning
confidence: 99%